Efektivitas Pembelajaran Daring Model Everyone Is a Teacher Here Dengan Google Meet Terhadap Hasil Belajar Geografi Peserta Didik Kelas X IPS Materi Pokok Perairan Laut di SMA Negeri 1 Baturetno Tahun Ajaran 2020/2021 - Clara Adhi Pratiwi Sukmana Dewi; Sarwono Sarwono; Singgih Prihadi (Universitas Sebelas Maret (UNS), 2022)
The objective of this research was to find out whether the ‘Everyone is a teacher here’ model using the Google Meet platform was effective in online learning toward the learning outcomes of Geography subjects in class X IPS with marine waters teaching materials at SMAN 1 Baturetno in the 2020/2021 academic year.This study was quasi-experimental research of the pretest-posttest type with quantitative research and was pseudo-experimental. The population was class X IPS SMAN 1 Baturetno academic year 2020/2021, and the samples were 72 students consisting of experimental and control classes. The data were collected through Google Form, provided to the students in both experimental and control classes. There were three stages of the research procedures: the measurement stage before the experiment, the implementation stage, and the measurement stage after the experiment.From the results of the study, it can be concluded that the ‘Everyone is a teacher here’ model using the Google Meet platform was more effective than the expository learning model in online learning toward the students of class X IPS’ learning outcomes in Geography subjects with marine waters teaching materials at SMAN 1 Baturetno academic year 2020/2021.Keywords : Everyone Is A Teacher Here, Geography Learning Outcomes.